A Novel Approach to the Implementation of Cloud-Based Quantum Programming Platforms in VR Environment - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
Quantum computers are becoming more and more powerful and practical each day with the perfection of the coherence time of superposition states and in terms of fidelity, error correction, power dissipation, and noise. Quantum computers have been used successfully in the solution of non-deterministic polynomial-time problems for a while. Using quantum algorithms to find ways to speed up the computing of some hard problems reveals a concept called quantum supremacy. With the improvement of quantum computers and a decrease in error rates, companies that develop quantum computers have offered cloud-based platforms to make their computers publicly available and to be programmed via the web. The cloud programming approach likewise influenced the programming of quantum computers. Here, we present that it is possible to use these platforms with VR sets, which are now becoming widespread in the field of education, and we try to introduce which tools are used in quantum cloud programming. © 2020 IEEE.
Keywords: cloud-based software; quantum circuit; quantum composer; Quantum computer; virtual reality browsers; VR headsets